Association between attention deficit hyperactivity disorder and chronotype in adults with epilepsy - Ugur, Kerim; Sun, Tunahan; Tasci, Irem; Kartal, Fatma (Cukurova Univ, Fac Medicine, 2025)
Purpose: This study aimed to determine the chronotype characteristics in adults with epilepsy, examine the relationship between chronotype and Attention Deficit Hyperactivity Disorder (ADHD), and compare ADHD symptom levels between patients with epilepsy and healthy controls. Materials and Methods: The study included 90 patients with epilepsy and 70 healthy controls, aged between 18 and 65 years. Sociodemographic and clinical data (seizure status, EEG, and MRI findings) were collected from the participants. The Morningness-Eveningness Questionnaire (MEQ), Adult ADHD Diagnosis and Evaluation Inventory, and Adult ADHD Self-Report Scale (ASRS) were administered. Results: A higher proportion of intermediate chronotypes was observed in the epilepsy group (68.9%) than in the control group (51.4%). ADHD symptom scores were higher in patients than in controls. Among patients with epilepsy, individuals with intermediate and evening chronotypes had significantly higher ADHD symptoms than those with morning chronotype. Although individuals with an evening chronotype had higher ADHD symptom levels than those with an intermediate chronotype, this difference was not statistically significant. Conclusion: The findings suggest that ADHD symptoms become more pronounced in patients with epilepsy as chronotype characteristics shift toward eveningness. Circadian features should be considered in the evaluation and management of ADHD comorbidity in adult patients with epilepsy.
Keywords: Adult epilepsy; ADHD , evening chronotype; circadian rhythm; neuropsychiatric comorbidity